Polymethyl Methacrylate Bone Cement Polymerization Induced Thermal Necrosis at the Cement–Bone Interface: A Narrative Review - Gergo Tamas Szoradi; Andrei Marian Feier; Sandor Gyorgy Zuh; Octav Marius Russu; Tudor Sorin Pop (Applied Sciences)
Polymethyl methacrylate (PMMA) bone cement has been a transformative material in orthopedics since its introduction in the mid-20th century. Originally used in dental medicine, PMMA was adopted for orthopedic applications by Sir John Charnley in the 1950s, significantly enhancing joint replacement surgeries. The primary appeal of PMMA lies in its biocompatibility, mechanical strength, and ease of handling, making it a favored choice for various orthopedic procedures, including arthroplasties and limb-salvage surgeries. However, the exothermic polymerization process of PMMA poses a risk of thermal necrosis in the surrounding bone tissue, as local temperatures can exceed 70 °C, causing damage to osteocytes. Research has sought to mitigate these risks by optimizing mixing techniques, reducing cement mantle thickness, and incorporating cooling methods. Recent advancements, such as the use of phase-change materials (PCMs) and alternative monomers, have shown promise in lowering the exothermic peak during polymerization. Other strategies include pre-cooling the cement and prosthetic components and using composite cement. Despite these innovations, managing the balance between minimizing heat generation and maintaining mechanical properties remains a challenge. The impact of thermal necrosis is significant, compromising implant stability and osseointegration. Understanding the complex interactions between PMMA’s thermal properties and its clinical outcomes is essential for improving orthopedic surgical practices and patient recovery.